Post-transcriptional regulation of cytokine and growth factor signaling in cancer. (February 2017) - Vlasova-St. Louis, Irina; Bohjanen, Paul R.
Graphical abstract: Highlights: Examination of published scientific data in the field of post-transcriptional regulation of cytokine and growth-factor signaling. AREs and GREs regulate mRNA turnover to coordinate cytokine and growth factor expression. Three RNA-binding proteins that competitively regulate mRNA stability through ARE and GRE are discussed. Dysregulation of mRNA degradation contributes to the development and progression of cancer. Abstract: Cytokines and growth factors regulate cell proliferation, differentiation, migration and apoptosis, and play important roles in coordinating growth signal responses during development. The expression of cytokine genes and the signals transmitted through cytokine receptors are tightly regulated at several levels, including transcriptional and post-transcriptional levels. A majority of cytokine mRNAs, including growth factor transcripts, contain AU-rich elements (AREs) in their 3′ untranslated regions that control gene expression by regulating mRNA degradation and changing translational rates. In addition, numerous proteins involved in transmitting signals downstream of cytokine receptors are regulated at the level of mRNA degradation by GU-rich elements (GREs) found in their 3′ untranslated regions. Abnormal stabilization and overexpression of ARE or GRE-containing transcripts had been observed in many malignancies, which is a consequence of the malfunction of RNA-binding proteins. In this review, we briefly summarize the role of AREs and GREs in regulating mRNA turnover to coordinate cytokine and growth factor expression, and we describe how dysregulation of mRNA degradation mechanisms contributes to the development and progression of cancer.